Design and Analysis of Rotor Assembly of Hammer Mill Machine - Akash Santosh Pawar (International Journal of Engineering and Management Research, 2021)
The project deals with the Manufacturing with Design and Analysis of Hammer Mill Machine and Rotor Assembly of Machine of Capacity of 200 Kg/hr. Which is due to providing the transmission power of 5 HP to the machine. In this project, the Hammer mill machine body structure, Angle Frame and foundation frame for machine is designed using Catia. Also each and every part or component is required for machine is designed. In the present work by using standard design procedures, Diameter of the rotor of shaft of machine has been designed. Theoretical calculations done by using PTC Mathcad software for new learning experience and ease. When the shaft of the rotor is rotated at the given speed (rpm i.e. 1728 rpm) and the load applied to the shaft it should not bend during rotation. When the shaft is rotated under free conditions deflections will be created due to critical speed of the shaft. After Designing process, some of required drawings are converted into Ansys supported format i.e. drawings are imported into Ansys for further analysis. Meshing of the shaft model was done and the loads, stresses that were applied for the shaft to be checked out that the design should be safe one. The design should be safe when the values obtained from the design procedure were compared with the standard values and result obtained from the analysis using Ansys. As per the designing, the required parts are fabricated such as side plates, bearing support, doors, hinge supports by using conventional methods like gas cutting, welding, drilling, shaft turning, slotting, milling, etc. and some hardware materials buy from stores which is used for further assembly process. At the final step all parts are assembled according as per requirements. At the end actual capacity of machine is calculated by using conventional method.